Learning English through Shadow Education: Exploring Participants’ Motives and Experiences - Hegedűs, Gabriella (Central European Journal of Educational Research, 2021)
Parallel to the institutionalised school system, in which no change in pedagogical attitudes has taken place (Einhorn 2015), there is a growing demand for learning languages in non-formal contexts, including out-of-school courses that not only complement students’ studies in formal education but also seem to make the process of learning languages as well as giving academic support to students more effective. The present study aims to explore the international and Hungarian literature on shadow education, which is widespread in Hungary but has little literature (Varga 2015), by presenting the characteristics of the phenomenon and highlighting its shortcomings. A qualitative study is also presented in order to examine the expectations and experiences of the students (and their families) participating in private tutoring. Data gleaned from interviews with students and their parents are analysed to identify their motives, expectations, the development of students’ additional skills and competencies, their career aspirations and the families’ financial background. The results of the study shed light on some characteristics of shadow education that have not been visible yet. Some factors that can potentially enhance the effectiveness of language teaching in the state school system will also be highlighted. Although the study is based on a rather limited sample, the results help us gain important insights into the hidden aspects of shadow education.